Interim storage of power reactor spent nuclear fuel (SNF) and its potential application to SNF separations and closed fuel cycle - Levy, Salomon (Nuclear engineering and design, 2009)
Interim, centralized, engineered (dry cask) storage facilities for USA light water power reactor spent nuclear fuel (SNF) should be implemented to complement and to offer much needed flexibility while the Nuclear Regulatory Commission is funded to complete its evaluation of the Yucca Mountain License and to subject it to public hearings. The interim sites should use the credo reproduced in Table 1 [Bunn, M., 2001. Interim Storage of Spent Nuclear Fuel. Harvard University and University of Tokyo] and involve both the industry and government. The sites will help settle the 50 pending lawsuits against the government and the $11 billion of potential additional liabilities for SNF delay damages if Yucca Mountain does not being operation in 2020 [DOE, 2008a. Report to Congress on the Demonstration of the Interim Storage of Spent Nuclear Fuel from Decommissioned Nuclear Power Stations (December)]. Under the developing consensus to proceed with closed fuel cycles, it will be necessary to develop SNF separation facilities with stringent requirements upon separation processes and upon generation of only highly resistant waste forms. The location of such facilities at the interim storage sites would offer great benefits to those sites and assure their long term viability by returning them to their original status. The switch from once-through to closed fuel cycle will require extensive time and development work as illustrated in “The Path to Sustainable Nuclear Energy” [DOE, 2005. The Path to Sustainable Nuclear Energy. Basic and Applied Research Opportunities for Advanced Fuel Cycles. DOE (September)]. A carefully crafted long term program, funded for at least 5 years, managed by a strong joint government–industry team, and subjected to regular independent reviews should be considered to assure the program stability and success. The new uncertainty about Yucca Mountain role raises two key issues: (a) what to do with the weapons and other high level government wastes committed to be moved to Yucca Mountain by specified dates? And (b) can the $13.6 billion invested at Yucca Mountain be salvaged if the NRC approves the license submittal and the opposition relents after contentious hearings? Or will it take contingent actions, or, a switch to a partial closed fuel cycle with its reduced risks and earlier timing of their peak risk value? Only time will tell if any of these alternates will be acceptable but, they all reinforce the need for interim storage for commercial SNF. If the decision is to go to a new repository one wonders whether the time has not come to change the safety evaluation process for geological repositories by characterizing two to three sites and subjecting them to an arbitrary release of the fission products in the HLW to be stored and considering the forms of some of the HLW to reduce their peak risks. It would allow the proper choice to be made among the selected sites and to have a basis for convincing the local committee to accept the repository location. It may even decide whether the CONFU fuel assembly [MIT, 2006. Implications of alternative strategies for transition to sustainable fuel cycles. Nucl. Sci. Eng., 154 (September)] for pressurized water reactors can be accommodated in a once-through fuel cycle as suggested by Levy [Levy, S., 2008. Yucca backup plan. Nucl. Eng. Int., 24–28]. A similar configuration is possible in boiling water reactors.